Three Flute Players’ Lived Experiences of Dalcroze Eurhythmics in Preparing Contemporary Music for Performance - Ridout, Rosalind; Habron, John (Frontiers in Education, 2020)
This qualitative study presents an interpretative phenomenological analysis of the lived experiences of three flute players who practise Dalcroze Eurhythmics, an approach to teaching, learning and understanding music through exploring various music-movement relationships in social, creative and rigorous ways. Our research seeks to understand how these individuals make sense of their lived experiences of Dalcroze Eurhythmics in learning, rehearsing and performing contemporary music. Data collected through semi-structured interviews were analysed and interpreted to create codes and categories in each data set. A cross-case analysis brought to light eight main themes: Body and breath; The body as a ‘way in’; Learning through the body overcomes specific technical difficulties; An embodied relationship with the score; Deeper knowledge and connection to music; Clarifying own interpretations; Communication with the audience; A bigger picture beyond the instrument. This study provides new insights into how learning through Dalcroze Eurhythmics can help individuals prepare repertoire for performance. As such, it may be of use to Dalcroze students and teachers, to flute performers and teachers, and to teachers and performers of other instruments who wish to explore the potential of Dalcroze Eurhythmics in learning, rehearsing and performing contemporary music. The analysis also reveals insights that may be relevant to other repertoires.